National Household Survey on Drug Abuse, 1991 ([Verlag nicht ermittelbar], 1993)
This series measures the prevalence and correlates of drug use in the United States. The surveys are designed to provide quarterly, as well as annual, estimates. Information is provided on the use of illicit drugs, alcohol, anabolic steroids, and tobacco among members of United States households aged 12 and older. Data are also provided on treatment for drug use and on illegal activities related to drug use. Questions include age at first use, as well as lifetime, annual, and past-month usage for the following drug classes: marijuana, inhalants, cocaine, hallucinogens, heroin, alcohol, tobacco, and nonmedical use of psychotherapeutics. Respondents were also asked about problems resulting from their use of drugs, alcohol, and tobacco, their perceptions of the risks involved, insurance coverage, and personal and family income sources and amounts. Demographic data include gender, race, ethnicity, educational level, job status, income level, household composition, and population density.